Mechanical and Antibacterial Properties of h-BN-TiO2 Nanocomposite-Modified Glass Ionomer Cement - Ma, Yu; Guo, Yan-Zhu; Liu, Yan; Wang, Yu-Rui; Yang, Jiang-Chuan; Kong, Xin-Zi; Jia, Hong-Lin; Li, Rui-Zhi; Han, Qi-Ze; Zheng, Cheng-Dong; Hu, Xin-Jun; Liu, Bin (Frontiers in Materials, 2022)
This study investigated the mechanical properties and antibacterial properties of hexagonal boron nitride and titanium dioxide (h-BN-TiO2) nanocomposite modified traditional glass ionomer cement. The mechanism of formation of the h-BN-TiO2 nanocomposite was elucidated by conducting molecular dynamics (MD) simulations using the Material Studio (MS) software. Furthermore, synthesis of h-BN-TiO2 nanocomposite by the original growth method using hexagonal boron nitride nanosheets (h-BNNs) and titanium dioxide nanoparticles (TiO2 Nps) and characterization using TEM and AFM to determine their particle sizes, morphologies, and structures. The mechanical properties and antibacterial efficacies of the glass ionomer cement composites were analyzed based on the different mass fractions (0, 0.3, 0.7, 1.1, and 1.5 wt.%) of the h-BN-TiO2 nanocomposite. The results showed that when the concentration of the h-BN-TiO2 nanocomposite was 1.1 wt.%, the Compressive strength (CS) and Vicker hardness (VHN) were 149.65% and 80.2% higher, respectively, compared to the glass ionomer cement without any h-BN-TiO2 nanocomposite. Also, the increase in the concentration of the h-BN-TiO2 nanocomposite led to a decrease in both the coefficient of friction (COF) and solubility, but a 93.4% increase in the antibacterial properties of the glass ionomer cement composites. The cell survival rate of each group was more than 70% after 48 h, but the difference was not statistically significant (P > 0.05). Therefore, the h-BN-TiO2 nanocomposite served as a reinforcing material for glass ionomer cement, which can be useful in clinical dentistry and provide a new strategy for improving the clinical utility of glass ionomer cement.